Simulation and validation of the effect of hydrostatic and non-hydrostatic pressure on contact pressure in a resilient seat butterfly valve - K Yuvaraj; G Arunkumar (Materials Research Express)
This study investigates the impact of hydrostatic and non-hydrostatic pressures on the contact pressure distribution in resilient-seated butterfly valves, a critical component in fluid control systems. Reliable sealing in such valves is essential to prevent leakage under varying pressure conditions. A 3-inch valve was analyzed under fully closed conditions with and without internal pressure. Finite Element Analysis simulated the contact pressure distribution at the disc-seat interface, revealing pressures ranging between 6.2 MPa and 12.9 MPa, which exceed the applied hydrostatic pressure, ensuring effective containment. Experimental validation included hydrostatic testing per API 598 standards and non-hydrostatic testing using prescale contact pressure films. Hydrostatic tests confirmed a leakage rate of 0 ml min ^−1 under low-pressure conditions, complying with API 598 requirements. Non-hydrostatic tests, performed with prescale films, recorded consistent pressure distributions in the range of 6 MPa to 10.5 MPa, verifying the EPDM seat’s effectiveness and uniform contact. The results confirm the valve’s ability to maintain leak-proof operation under both hydrostatic and non-hydrostatic pressures, validating FEA predictions and reducing reliance on time-intensive physical testing. These findings emphasize the robustness of resilient-seated butterfly valve design and its optimization for industrial applications, improving operational reliability and enhancing simulation accuracy in fluid control systems.